Non-Extraction Orthodontic Camouflage for Severe Class II Malocclusion Post-TMJ Gap Arthroplasty: A Case Report - Eser Rengin Nalbantoglu; Sina Uckan; Parmjit Singh (Oral, 2025)
Background/Objectives: Orthodontic camouflage is a treatment strategy designed to address mild to moderate skeletal discrepancies through dental compensation when growth modification or orthognathic surgery (OGS) is unsuitable or declined by the patient. This report highlights the treatment of a child with a skeletal Class II pattern, Class II division 1 malocclusion, a 10.8 mm overjet, traumatic overbite, and unilateral temporomandibular joint (TMJ) ankylosis on the left side. Methods: The treatment plan focused on correcting the proclination of the maxillary incisors and improving the facial profile. A non-extraction camouflage approach using pre-adjusted edgewise appliances was implemented following a gap arthroplasty procedure on the left TMJ. Results: The patient achieved a satisfactory treatment outcome, with an ideal static and functional occlusion and significant improvement in facial esthetics. The approach effectively managed the severe mandibular retrognathia and TMJ ankylosis without OGS, thereby minimizing the risk of progressive condylar resorption. Conclusions: This case underscores the importance of personalized treatment plans tailored to each patient’s dental, skeletal, and individual needs. It demonstrates that non-surgical camouflage treatments can be a viable alternative for addressing severe mandibular retrognathia with TMJ ankylosis, achieving favorable esthetic and functional outcomes.